Perceptions of Housing and Shelter among People with Histories of Unstable Housing in three Cities in Canada: A Qualitative Study. Issue 3 (25th March 2018) - Sylvestre, John; Klodawsky, Fran; Gogosis, Evie; Ecker, John; Polillo, Alexia; Czechowski, Konrad; Agha, Ayda; Shankar, Sneha; To, Matthew; Gadermann, Anne; Palepu, Anita; Hwang, Stephen
Abstract: Housing is a key social determinant of health that contributes to the well‐documented relationship between socioeconomic status and health. This study explored how individuals with histories of unstable and precarious housing perceive their housing or shelter situations, and the impact of these settings on their health and well‐being. Participants were recruited from the Health and Housing in Transition study (HHiT), a longitudinal, multi‐city study that tracked the health and housing status of people with unstable housing histories over a 5‐year period. For the current study, one‐time semi‐structured interviews were conducted with a subset of HHiT study participants ( n = 64), living in three cities across Canada: Ottawa, Toronto, and Vancouver. The findings from an analysis of the interview transcripts suggested that for many individuals changes in housing status are not associated with significant changes in health due to the poor quality and precarious nature of the housing that was obtained. Whether housed or living in shelters, participants continued to face barriers of poverty, social marginalization, inadequate and unaffordable housing, violence, and lack of access to services to meet their personal needs. Highlights: A unique examination of the living conditions of people who have histories of housing instability. Study of perceptions of housing among vulnerably housed people in three Canadian cities. A qualitative study of the links between precarious housing and health.